Preliminary evaluation of ORYZA (v3) crop growth model for MR269 rice variety - Che Hashim, Muhamad Faiz; N. Y., Liyana; Khairudin, Nurulhuda; Muharam, Farrah Melissa; Zulkafli, Zed Diyana; Berahim, Zulkarami; Ismail, Mohd Razi (Malaysian Society of Agricultural Engineers, 2019)
Rice (Oryza sativa) is a staple food for more than half of the world’s population, including about 30 million Malaysians. Rice self-sufficiency level (SSL) in Malaysia is currently at 70% and the level does not satisfy the local demand. Therefore, rice production needs to be increased to 80% by the year 2020 (MOA, 2015). The Malaysian Government aims to increase average rice grain production from 4.5 mt/ha to 6.0 mt/ha (Ismail, 2017). Among the ways to increase the production of rice is by improving crop management, such as finding best sowing dates, and best management practices such as optimum usage of fertilizer rates and rice varieties that suit weather conditions. Simulations of crop models are alternatives to costly trial experiments in exploring opportunities for increasing agricultural system productivity. Existing rice crop growth models have not been rigorously explored to assess productivity of Malaysian rice systems. Prior to scenario studies using a rice crop growth model, performance of the model must first be evaluated. Therefore, this paper reports preliminary evaluation on the performance of a rice crop growth model called ORYZA (v3). The model was evaluated against rice crop physiological properties collected at two farmers’ plots at IADA KETARA, Terengganu. The preliminary evaluation indicates that ORYZA (v3) has a potential in simulating the physiological properties of MR269, but the model must be calibrated. Calibration of the model is currently on-going.